Masculinity and the feminist position of women in one of Maryam Jahani's novels and its traces in Iranian paintings - Tahereh Rezvani; Ali Dehghan; Hamidreza Farzi (هنر اسلامی, 2022)
Masculinity is one of the key concepts of feminist tendencies. Feminists believe that in a patriarchal society, men have superior power and authority over women. They attribute the inferiority of women in a patriarchal society to men's greater access to the benefits of power structures, the unequal distribution of social privileges, and the mismanagement of men and women. The issue of patriarchy is reflected in literary texts. Many works have been written with this approach, especially in the field of novel writing. The first objections and criticisms to this inequality were made by women in the field of literature. Among Persian language writers, Maryam Jahani has written the novel "This Street Has No Accelerator" with a feminist perspective. The feminist manifestations and characteristics of this novel, first because of its woman-centeredness, then the militant tendency of this novel with the patriarchal system, has made it one of the feminist novels. The purpose of this article is to examine anti-patriarchal actions in the global novel. A descriptive-analytical study of the novel shows that the world has depicted the factors of domination in the patriarchal system and the methods of women's struggle in it. Factors arising from culture and tradition in this novel are contrasted with feminist modernity.